OPTIMIZING CAMPUS PROMOTION THROUGH ADVERTISING PHOTOGRAPHY AT THE POLITEKNIK NEGERI MEDIA KREATIF - Syaputra, Dadang (Jurnal Ilmiah Publipreneur, 2025)
Politeknik Negeri Media Kreatif PSDKU Medan faces challenges in increasing visibility and attractiveness to prospective new students due to the less than optimal promotional strategy in digital media, especially on the Instagram platform. This study aims to develop promotional visual content by utilizing three-point lighting-based advertising photography techniques to improve the quality and effectiveness of campus promotional media. The method used is descriptive qualitative research with a case study approach on the campus's official Instagram account. Data were obtained through observation, interviews, and documentation, then analyzed qualitatively to describe changes in visual quality and audience response. The results of the study show that the application of professional three-point lighting techniques in advertising photography can improve visual aesthetics and content consistency, so that the content becomes more attractive and relevant to the target audience of teenagers aged 17–21 years who are interested in the creative industry. This increase in visual quality has an impact on increasing interactions on social media and strengthening the positive image of the campus, which ultimately increases awareness and interest of prospective students in Polimedia PSDKU Medan. In addition, the resulting photographic works also have the potential to be used as visual assets across communication channels to support long term promotions.